Study anti-inflammatory effect of Tamsulosin in rat by evaluation IL-4, IL-6 and TNF-α: airway model. - Alabdali, Hala; Algaem, Manal (Iraqi Journal of Pharmaceutical Sciences, 2023)
Background: Inflammatory airway disease is a well-known worldwide health problem. Available medication is accompanied by dangerous side effects and only provides temporary symptom control. Aim: To investigate the effect of tamsulosin, on the pro-inflammatory cytokines IL-4, IL-6, and TNF-α that are associated with airway inflammation. Method: male, albino rats (n=30), weighing (150-250 gm) were allocated into (5) groups, each group with (6) rats; Group A: normal control group, rats were given distilled water for 14 days. Group B: negative control group, rats exposed to airway sensitization only. Group C: positive control group, treated with prednisolone (4.12mg/kg/d) orally plus airway sensitization. Group D: treated control group with tamsulosin (35 mcg/kg/d) orally plus airway sensitization. Group E: treated control group with tamsulosin (17.5 mcg/kg/d) orally plus airway sensitization. Measurement of inflammatory cytokines IL- 4, IL-6, and TNF-αin serum samples by ELISA. Results: there was a significant reduction (P-value<0.05) of IL- 4 and TNF-α in serum for tamsulosin treated group (D) and group (E) when compared with the positive control group (B). But only group(D) 35mcg/kg/d tamsulosin showed significant reduction(P-value<0.05) in IL-6 level when compared with positive control group (B). Conclusion: Tamsulosin has an anti-inflammatory effect by reduction of IL-4, IL-6, and TNF-α in the rat airway model.